Coherent control of a surface structural phase transition - Horstmann, Jan Gerrit; Böckmann, Hannes; Wit, Bareld; Kurtz, Felix; Storeck, Gero; Ropers, Claus (Nature (London), 2020)
Active optical control over matter is desirable in many scientific disciplines, with prominent examples in all-optical magnetic switching 1 , 2 , light-induced metastable or exotic phases of solids 3 – 8 and the coherent control of chemical reactions 9 , 10 . Typically, these approaches dynamically steer a system towards states or reaction products far from equilibrium. In solids, metal-to-insulator transitions are an important target for optical manipulation, offering ultrafast changes of the electronic 4 and lattice 11 – 16 properties. The impact of coherences on the efficiencies and thresholds of such transitions, however, remains a largely open subject. Here, we demonstrate coherent control over a metal–insulator structural phase transition in a quasi-one-dimensional solid-state surface system. A femtosecond double-pulse excitation scheme 17 – 20 is used to switch the system from the insulating to a metastable metallic state, and the corresponding structural changes are monitored by ultrafast low-energy electron diffraction 21 , 22 . To govern the transition, we harness vibrational coherence in key structural modes connecting both phases, and observe delay-dependent oscillations in the double-pulse switching efficiency. Mode-selective coherent control of solids and surfaces could open new routes to switching chemical and physical functionalities, enabled by metastable and non-equilibrium states. A structural phase transition from metal to insulator on a solid surface is controlled by an ultrafast sequence of optical pulses.